KITA-ESD and KIVSA Leadership Typologies: The Role of Influencer Leadership, Islamic Performance, and Dedication in Developing Leading Schools - Suci Hidayati; Sri Harini; Abdul Malik Karim Amrullah; Agus Maimun (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Education currently faces significant challenges, including global competition, rapid digital transformation, increasing demands for quality improvement, and the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. This study aims to quantitatively and qualitatively analyze the extent to which influencer leadership affects Islamic performance and dedication, as well as its contribution to the development of ESD-based flagship schools. Additionally, this research explores leadership typologies as an emerging model relevant to 21st-century Islamic educational institutions. This study employed a mixed-method approach using Structural Equation Modeling (SEM) across four ESD-based schools in Malang Regency. Data were collected through a survey involving 100 respondents, including school principals, teachers, and educational staff. A pragmatic model with an expansive design was utilized, combining statistical analysis with qualitative exploration through observations, interviews, and document analysis. The findings indicate that influencer leadership has a positive and significant effect on enhancing Islamic dedication and performance, with a p-value of 0.00, and directly contributes to the establishment of superior schools. Islamic dedication plays a crucial role in strengthening institutional quality, while Islamic performance, although not directly significant (p-value 0.136), supports operational success. Furthermore, two leadership typologies were identified: KITA-ESD (Aswaja Transformational Influencer Leadership) and KIVSA (Aswaja Spiritual Visionary Influencer Leadership). These findings highlight that institutional success depends not only on infrastructure but also on leadership strength, Islamic work culture, and collective commitment.